Performance, Preferences and Policies in Urban Water Supply in Yogyakarta, Indonesia - Boedihardja, Y.K. (CRC Press, 2020)
Indonesia, as a developing country, faces all these problems. In most Indonesian cities, the local PDA M (Perusahaan Daerah Air Minum, or Piped Water Supply Company) provides drinking water. Large portions of the population, however, do not use these services, and for a variety of reasons depend on groundwater sources instead.